LESS CARE, MORE STRESS: A RHYTHMIC POEM FROM THE ROMAN EMPIRE. (December 2021) - Whitmarsh, Tim
Abstract : This article considers a short text that was widely circulated in the mid- Roman Empire, in both a four-line and a six-line version, usually on gemstones. The text is a poem of sorts, but of a quite distinctive type. Part of it can be scanned according to the rules of classical (quantitative) metre, but more striking is the consistent rhythmic (stressed) pattern. Stressed poetry is not otherwise attested so early; this text may point to a substrate, now largely hidden from view, of popular verse that preceded the metrical revolutions of late antiquity and the Byzantine world. The poem is also a piece of visual artistry, designed to be looked at (particularly in its gemstone format). This hybrid status, between high art and popular culture, can also be detected in the content of the poem, which gestures towards both the poetics of intellectual elitism (using intertextual allusion, and dismissing the views of the masses) and a level of sexually aggressive assertion of embodied selfhood. It is a valuable witness to a form of middling literature (and a middling demographic), caught between aspirations to elite-style individuality and the mimetic imperative of an empire-wide consumer culture.